The Influence of E-WOM, Perceived Self-Efficacy, and Herding Behavior on Online Purchase Intentions During Shopee Live Streaming of Fashion Products in Denpasar City - I Wayan Deni ARMIKA; Nengah GANAWATI; Ni Ketut SARIANI (Loka: Journal Of Environmental Sciences, 2024)
Purpose:Online purchase intention for a product is determined by several indicators. "The purpose of this study was to determine the simultaneous and partial influence of e-WOM, perceived self-efficacy, and herding behavior on online purchase intention during Shopee live streaming of fashion products in Denpasar City.Methodology:The population in this study was all Shopee app users in Denpasar City, with an unknown exact number. A purposive sampling method determined the sample size at 100. Data collection was conducted using a questionnaire. The collected data were analyzed using multiple linear regression, while hypotheses were tested using the F-test and t-test.Findings:The results of this study indicate that E-WOM, perceived self-efficacy, and herding behavior have a simultaneous positive effect on online purchase intention on Shopee live streaming of fashion products in Denpasar City. E-WOM has a partial positive effect on online purchase intention on Shopee live streaming of fashion products in Denpasar City.Implication:Perceived self-efficacy has a partial positive effect on online purchase intentions on Shopee live streaming of fashion products in Denpasar City, and Herding behavior has a partial positive effect on online purchase intentions on Shopee live streaming of fashion products in Denpasar City.